Immunoinformatic identifcation of B cell and T cell epitopes in the SARS‐CoV‐2 proteome (2020)
A novel coronavirus (SARS-CoV-2) emerged from China in late 2019 and rapidly spread across the globe, infecting millions of people and generating societal disruption on a level not seen since the 1918 infuenza pandemic. A safe and efective vaccine is desperately needed to prevent the continued spread of SARS-CoV-2; yet, rational vaccine design eforts are currently hampered by the lack of knowledge regarding viral epitopes targeted during an immune response, and the need for more in-depth knowledge on betacoronavirus immunology. To that end, we developed a computational workfow using a series of open-source algorithms and webtools to analyze the proteome of SARS- CoV-2 and identify putative T cell and B cell epitopes. Utilizing a set of stringent selection criteria to flter peptide epitopes, we identifed 41T cell epitopes (5 HLA class I, 36 HLA class II) and 6 B cell epitopes that could serve as promising targets for peptide-based vaccine development against this emerging global pathogen. To our knowledge, this is the frst study to comprehensively analyze all 10 (structural, non-structural and accessory) proteins from SARS-CoV-2 using predictive algorithms to identify potential targets for vaccine development.